What is the Current Knowledge and Experience on Preventive Pathway for Healthy Ageing in Italy? A Scoping Review - Masini, Alice; Pighini, Irlanda; Conti, Andrea; Isabella, Antonio; Cherasco, Niccolò; Panella, Massimiliano (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
Background. Worldwide population is ageing rapidly. Lifestyle factors are essential targets for leading to behaviour change interventions that promote healthy aging.Study design. We performed a scoping review aimed to underline the current knowledge and experience on preventive interventions for healthy and active ageing in Italy. Secondly, it intended to study the manner in which this country will pursue the topic in this research area.Methods. The search was conducted on different databases: PubMed, CINAHL, Embase, and Scopus on July 25th, 2023, and search results were filtered to include only articles published from 2003.Results. A total of 951 potentially relevant records were retrieved. After duplicates removal, 810 unique records were screened. Finally, four studies fulfilling established criteria were included. All the studies were conducted in the northern and central regions of Italy. The investigated populations were older adults, and all four studies were focused mainly on primary prevention and health promotion strategies based on self-efficacy and motivation of the participants, including physical activity, diet and cognitive training. In addition, two studies used mobile health technologies to deliver the preventive intervention for healthy ageing.Conclusion. Our scoping review underlines the limited knowledge and experience of preventive healthy aging interventions in the national setting. The new preventive pathway that promotes healthy ageing healthily should be based on tailored lifestyle interventions, managed by multidisciplinary teams with the use of digital tools, in order to improve older people’s safety. The character